IoT-Based Obstacle Detection System for Visually Impaired Person with Smartphone Module - Jasman N.A.; Jalil M.F.I.M.; Mukhtar A.; Sahari K.S.M.; Rusli M.E. (Engineering and Technology Publishing, 2023)
Visually impaired persons face several challenges in their daily lives. In many cases, they are usually dependent on others, making them less confident in an unfamiliar environment. Therefore, this article presents an IoT-based system that helps to detect obstacles and water puddles on their way. The system consists of a walking stick and an Android app from a third-party app. The walking stick is integrated with an ESP32 microcontroller, an ultrasound sensor, and an app for smartphones. The sensors gather information from the surroundings, and the ESP32 microcontroller detects the obstacle by processing the information. The communication between the ESP32 microcontroller and the smartphone is carried out through the MIT App Inventor. The smartphone application generates audible instructions to navigate the visually impaired persons properly. The results indicated that the developed system obtained an accuracy of about 99.54% at a distance of 250cm and 99.03% at a distance of 450cm. The system also sensed an obstacle angular position of up to 90. Thus, it shows that this system has been very effective and efficient for visually impaired persons to navigate with precise voice instructions. Overall, the system developed would help visually impaired person independent lives safely, which will ultimately increase their level of confidence in an unfamiliar environment. 2022 J. Adv. Inf. Technol. and 2022 by the authors.